Optimization Of Vehicle Suspension System In Road Roughness - Tee, Boon Tuan; Gan, Chin Kim (2005)
This paper is proposed to predict the ride quality of a specific road vehicle responding to ground irregularity (road roughness). Based on this prediction, the suspension characteristics of the vehicle an be optimized. This is implemented by using MATLAB-SIMULINK. Three types of models are being evaluated which consist of a single-degree of freedom model, two-degree of freedom model and car with tyre suspension system. The optimization of the suspension characteristic is evaluated by reviewing the Mean Square Response (MSR) of the vehicle displacement with parameters relating to the vehicle suspension. The results, which are presented on this paper shows that by increasing the degree of freedom in a suspension system, the accuracy of the result will also increase.